Decision satisfaction among women choosing a method of pregnancy termination in the setting of fetal anomalies and other pregnancy complications: A qualitative study. Issue 10 (October 2018) - Kerns, Jennifer L.; Light, Alexis; Dalton, Vanessa; McNamara, Blair; Steinauer, Jody; Kuppermann, Miriam
Highlights: Women with pregnancy complications often elect to terminate the pregnancy. Surgical and medical procedures are safe and effective for pregnancy termination. Choosing a termination method is a preference-sensitive decision. Decision satisfaction is tied to patients' values, information about the procedure, and exercising choice of method. A values-based decision aid may support women choosing a termination method. Abstract: Objective: The decision to undergo a surgical or medical method of second-trimester termination for pregnancy complications should be preference-sensitive. Decision satisfaction has not been described in this population; understanding how women describe decision satisfaction in this setting could inform decision support efforts. Methods: We conducted qualitative interviews with women one to three weeks after termination who chose either a surgical or medical termination for fetal anomalies, pregnancy complications or fetal demise. We analyzed transcripts using modified grounded theory in an iterative manner with a generative thematic approach. Results: We interviewed 36 women (24 surgical and 12 medical). Subjects connected decision satisfaction with counseling experiences and their personal values, including (1) importance of adequate information, (2) autonomous decision making, and (3) choosing the method that facilitates coping. Conclusion: Offering women a choice between surgical and medical termination procedures in the setting of pregnancy complications is integral to decision satisfaction. Women in our study reported wanting this decision to be driven by their personal values. Practice implications: : Women should be able to choose between surgical and medical termination based on preference and not availability of services. Decision support from women's health providers should be based on values clarification and providing accurate information.